Effects of Grape Seed Extract, Vitamin C, and Vitamin E on Ethanol- and Aspirin-Induced Ulcers - Vivian Molina Cuevas; Yazmín Ravelo Calzado; Yohani Pérez Guerra; Ambar Oyarzábal Yera; Sonia Jiménez Despaigne; Rosa Mas Ferreiro; Daisy Carbajal Quintana (Advances in Pharmacological Sciences)
Effects of GSE and vitamins C and E on aspirin- and ethanol-induced gastric ulcer and associated increases of lipid peroxidation in rats were compared. Two experiments were conducted. Rats were randomized into eight groups: a negative control and seven groups that received aspirin or ethanol for ulcer induction: one positive control (vehicle) and six with VC, VE, or GSE (25 and 250 mg/kg). Ulcer indexes and gastric levels of malondialdehyde (MDA) were quantified. VC, VE, and GSE (25 and 250 mg/kg) decreased aspirin, and ethanol-induced ulcers and MDA values compared with positive control group. The magnitude of aspirin ulcer reduction was comparable for all treatments, and MDA decrease with GSE was higher than with VC and tended to be greater, albeit none significantly, than with VE. GSE was more effective than VC and VE for lowering the ethanol ulcers, while the decrease of MDA levels with GSE was greater than with VC, but comparable to that achieved with VE. GSE protected against ethanol-induced gastric ulcers more effectively than VC or VE, while its protection against aspirin ulcers was comparable for all treatments. GSE produced the greatest reductions of gastric MDA in both models.